Pengaruh Penggunaan Alat Peraga terhadap Pencapaian Hasil Belajar Matematika dalam Materi Pembagian di sekolah Dasar - Husna Nabila; Aina Salsabila; Kowiyah Kowiyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to examine the impact of using visual aids on students' mathematics achievement in division material at the elementary school level. The method implemented was a quasi-experiment using a pretest-posttest group design. The subjects of this study were third-grade elementary school students, divided into two groups: the experimental group, which used visual aids, and the control group, which applied conventional methods. The study's findings indicate that the experimental group, which applied visual aids, showed a significant improvement in mathematics achievement, particularly in division material. The average pretest score of the experimental group was 75.2, while the posttest score increased to 80.9. Based on data analysis, it can be concluded that the use of visual aids has a positive impact on students' mathematics achievement in division material.